The effect of benign epileptiform discharges of childhood on cognitive function, behavior and speech - E. A. Morozova; M. V. Belousova; D. V. Morozov; M. A. Utkuzova (Эпилепсия и пароксизмальные состояния)
The article presents a case  report, and a literature review on benign epileptiform  discharges of childhood (BEDC) as well as effect of this type of epileptiform activity on speech, behavior and communication skills are analyzed. The incidence of BEDC comprises 5% in pediatric population.  Examining children with autistic spectrum disorder, BEDC is revealed  in 20% cases, whereas  in those with attention deficit and hyperactivity disorder  (ADHD) or speech  disorder  – in 25% and 18% cases, respectively.  Many studies  considering BEDC as  a  genetic marker of  brain immaturity highlighted by  different level of expressiveness and penetrance are discussed. It is highly probable that cognitive and speech disorders as well as ADHD in children with BEDC may be genetically determined. However, pediatric BEDC may be asymptomatic or become  manifested by diverse psychoneurological symptoms accounted for by developed epileptic encephalopathy and continuous spike and waves during slow wave sleep (CSWS)  requiring specialized long-term treatment. Markedly elevated  CSWS with morphological BEDC affects interneuron connections, which, in turn, alters memory consolidation in mesial temporal regions. The literature analysis  revealed  that children  with BEDC-like epileptic activity require obligatory periodic sleep electroencephalographic control  and dynamic  neuropsychological  evaluation due to  high incidence  of speech, mnestic  and behavioral disorders. Seizure-free BEDC-like epileptic activity should be corrected pharmaceutically only in case  of established  causative link with progressive cognitive impairments.